If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -1u)(5u + 4) = 0 Reorder the terms: (6 + -1u)(4 + 5u) = 0 Multiply (6 + -1u) * (4 + 5u) (6(4 + 5u) + -1u * (4 + 5u)) = 0 ((4 * 6 + 5u * 6) + -1u * (4 + 5u)) = 0 ((24 + 30u) + -1u * (4 + 5u)) = 0 (24 + 30u + (4 * -1u + 5u * -1u)) = 0 (24 + 30u + (-4u + -5u2)) = 0 Combine like terms: 30u + -4u = 26u (24 + 26u + -5u2) = 0 Solving 24 + 26u + -5u2 = 0 Solving for variable 'u'. Factor a trinomial. (6 + -1u)(4 + 5u) = 0Subproblem 1
Set the factor '(6 + -1u)' equal to zero and attempt to solve: Simplifying 6 + -1u = 0 Solving 6 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1u = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1u = 0 + -6 -1u = 0 + -6 Combine like terms: 0 + -6 = -6 -1u = -6 Divide each side by '-1'. u = 6 Simplifying u = 6Subproblem 2
Set the factor '(4 + 5u)' equal to zero and attempt to solve: Simplifying 4 + 5u = 0 Solving 4 + 5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5u = 0 + -4 5u = 0 + -4 Combine like terms: 0 + -4 = -4 5u = -4 Divide each side by '5'. u = -0.8 Simplifying u = -0.8Solution
u = {6, -0.8}
| 1.087x=49 | | x*1.087=60 | | 91=x*7 | | log(2x-5)(x+2)=2 | | x*1.087=48 | | x*1.087=50 | | x*0.87=50 | | 2y^2+2y-2=0 | | 8x+2y=45-x | | 23b+0.25=3.20 | | -.5+.125= | | ln(x+1)+ln(x)-ln(2)=0 | | 6-6x=-6x+6 | | 10x-6=4+5x | | 24-x^2-12x=0 | | f(x)=10x^4+7x^3-27x^2+2x+8 | | x^2+3x-1=17 | | (4x+11)+(3x+1)=180 | | (x-2)(x-2)(1)=169 | | 21x=3/4 | | (x+10)+(3x+18)=180 | | -20(3x-68)=-80(9x-38) | | (2x-5)+(4x-13)=90 | | 3x+7z=2-2y | | 4a^2=25a+21 | | 7(a-6)+13=3(a-7) | | 4(x+5)-3=23-2x-6+6x | | 7a-7a=15 | | 7(-6)+3y=12 | | 240=2x^2+2x | | 33%+14%= | | 10(x+5)=3(4x+3) |